Transient Cerebral Ischemia Leads to TGF-β2 Expression in Golgi Apparatus Organelles - Hu, Zhiping; Fan, Jie; Zeng, Liuwang; Lu, Wei; Tang, Xiangqi; Zhang, Jie; Li, Ting (Current Neurovascular Research, 2008)
Transforming growth factor2 (TGFβ2) is a prototypic member of a large superfamily of multifunctional cytokines, and its potential mechanisms of the neuroprotective activity in ischemic stroke and subcellular compartmentalization are largely unknown. The present study investigated TGF-β2 protein expression in hippocampal neuronal cells after transient forebrain ischemia (TFI). TFI was induced in male adult gerbils with bilateral occlusion of both common carotid arteries for 10 minutes. With immunohistochemical methods we observe the expression of TGF-β2 and morphological alternation in Golgi appratus (GA) in different postischemic periods and sham-operation (6 hours, 1, 3 and 7 days). In addition, the subcellular localization of TGF-β2 is determined in trans-Golgi network (TGN) by doublelabeling confocal immunofluorographs with TGN38.The results showed that TGF-β2 persistent express in the ischemic animals and it peaks at 3 days, then decreased 7 days postocclusion. No significant alterations to the GA were noted at the point of 6 hours,1 and 3 days following TFI, but there are a few neurons in which the GA lost the normal network-like configuration and its elements decreased in cortical cells from gerbils survived 7 days postocclusion. In addition, TGF-β2 was colocalized with TGN38 in the TGN after TFI .Taken together, this result suggested that TGF-β2 protein expression increased in neurons after ischemia, which may represent an endogenous adaptative response of the brain damage and its secretion via GA after ischemia is supposed to be beneficial for GA . Furthermore, fragmentation of GA is not common phenomenon in the ischemia, but intact GA structural of neurons is beneficial for cell survival.
Keywords: Ischemia